2004
DOI: 10.1093/aje/kwh101
|View full text |Cite
|
Sign up to set email alerts
|

Limitations of the Odds Ratio in Gauging the Performance of a Diagnostic, Prognostic, or Screening Marker

Abstract: A marker strongly associated with outcome (or disease) is often assumed to be effective for classifying persons according to their current or future outcome. However, for this assumption to be true, the associated odds ratio must be of a magnitude rarely seen in epidemiologic studies. In this paper, an illustration of the relation between odds ratios and receiver operating characteristic curves shows, for example, that a marker with an odds ratio of as high as 3 is in fact a very poor classification tool. If a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

16
837
3
7

Year Published

2005
2005
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,075 publications
(863 citation statements)
references
References 25 publications
16
837
3
7
Order By: Relevance
“…However, limitations of the use of ROC-AUCs for determination of the predictive value of biomarkers have been addressed [27]. High odds ratios are needed for an individual biomarker to improve the ROC-AUC [28]. Furthermore discrimination, measured by the ROC-AUC, determines the probability of a case being assigned a higher risk than a control, whereas classification assesses the The x-axis represents the predicted probability of death for the model using only the APACHE IV score, the y-axis for the model with APACHE IV and suPAR combined.…”
Section: Discussionmentioning
confidence: 99%
“…However, limitations of the use of ROC-AUCs for determination of the predictive value of biomarkers have been addressed [27]. High odds ratios are needed for an individual biomarker to improve the ROC-AUC [28]. Furthermore discrimination, measured by the ROC-AUC, determines the probability of a case being assigned a higher risk than a control, whereas classification assesses the The x-axis represents the predicted probability of death for the model using only the APACHE IV score, the y-axis for the model with APACHE IV and suPAR combined.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been shown that a risk factor must have a much stronger association with the disease outcome (very large RR) than we ordinarily see in etiologic research for it to be a worthwhile screening test, that is, be capable of efficiently discriminate between persons likely to have the outcome and those who do not (good sensitivity and specificity). (31)(32)(33) Our study has several strengths and limitations. An extensive amount of data were collected for each woman at the baseline and follow-up visits, including the use of osteoporosis medications and HRT throughout the follow-up, which allowed us to examine a large set of potential CRFs for fracture.…”
Section: Discussionmentioning
confidence: 99%
“…In two studies [21,62], it was necessary to recalculate these figures using the raw numbers presented. Diagnostic odds-ratio's (DOR's) were not calculated because of the recent suggestion that a DOR does not meaningfully describe a marker's ability to classify subjects [41]. A meta-analysis was also not Table 1 Methodological criteria used to assess the quality of studies investigating diagnostic accuracy for subjects with cervical radiculopathy Item 1.…”
Section: Discussionmentioning
confidence: 99%